King James I and the religious culture of England - Doelman, James, 1963- (Studies in Renaissance literature (Woodbridge, Suffolk, England) ;, 2000)
James I and the Religious Culture of England is a study of King James's influence, both direct and indirect, on various aspects of religious life in England during his reign. The book begins with an examination of the roots of James's religious thinking in the Protestant understanding of biblical monarchy, and his own experiences as king of Scotland, before turning to its main focus of James's English reign.